Reproductive health in the recent disasters of Iran: a management perspective - Sanaz Sohrabizadeh; Katayoun Jahangiri; Reza Khani Jazani (BMC, 2018)
Abstract Background Natural disasters represent critical threats to the health, safety, and well-being of a community-including reproductive health, which has been neglected in disaster-stricken regions. The current study was undertaken to explore administrative issues related to post-disaster reproductive health systems in Iran. Methods A qualitative approach using in-depth unstructured interviews was applied to explore the administrative issues of reproductive health systems in the affected regions. A total of 22 participants were interviewed using the purposeful sampling method. Data were collected in three provinces: East Azerbaijan, Bushehr, and Mazandaran. Transcribed interviews were analyzed using the conventional content analysis. Results Six categories of management issues of reproductive health in disasters were extracted from data. These categories were: ignoring cultural factors, lack of planning, lack of training, insufficient data collection, ignoring male reproductive health, and lack of monitoring systems. Conclusion Different challenges to reproductive health management that emerged from the research should be considered and included in reproductive health plans and policies in disaster-affected regions in Iran. Involving community in all processes of providing reproductive health services, from planning to monitoring, is highly suggested.